Effects of FK228, a novel histone deacetylase inhibitor, on tumor growth and expression of p21 and c-myc genes in vivo - Sasakawa, Yuka; Naoe, Yoshinori; Inoue, Takeshi; Sasakawa, Tatsuya; Matsuo, Masahiko; Manda, Toshitaka; Mutoh, Seitaro (Cancer letters, 2003)
In this study, we examined the effects of FK228 (FR901228, depsipeptide) on tumor growth and expression of p21 and c-myc genes in vivo. FK228 induced the expression of p21 mRNA and decreased c-myc mRNA in tumor xenograft sensitive to FK228. However, FK228 did not sufficiently modulate the expression of p21 mRNA and increased the expression of c-myc in tumor xenograft less sensitive to FK228. The modulation of p21 and/or c-myc genes may be critical for the marked antitumor activity of FK228 in vivo.